The effect of training program using a sports breathing mask on the special physiological variables and the level of performance of some offensive skills of the fencing players - Dr. Isam Mansoor Mohin Alhameed (Global Scientific Publishing, 2023)
The research aims to identify the effect of a training program using a sport breathing mask on the special physiological variables and the level of performance of some offensive skills of the fencing players , where the experimental approach was used using the experimental design for one experimental group , using the pre and post measurement due to its suitability to the nature of research , the research sample was chosen by the intentional method their number reached (10) rowing club fincing Alexandria under the age of 18 season 2022 AD the experimental research group was training using a breathing mask during the preparation period within the training program , for a period of twelve weeks with(3) weekly training units with a total 36 training units time the unit is (90) minutes the results showed that wearing a breathing mask during the training program led to an improvement in physiological variables ( vital capacity – respiratory rate after exertion – maximum oxygen consumption – pulse rate at rest – pulse rate after exertion , systolic blood pressure – diastolic blood pressure ) and the improvement of the skill variables under study (the straight attack – the raiding attack – the categorical attack ) and the researcher recommends Ert Respirator mask disease in training programs because of its positive impact on developing the functions of vital organs , especially the circulatory and respiratory system and delaying the onset of fatigue for fencing players Genders
Keywords: training program; sports breathing mask; special physiological variables